Understanding the petrophysical properties, seismic responses and impacts of the basalt-sediment transition in prospective sedimentary basins - Natália Famelli; John Millett; Malcolm Hole; Dougal A. Jerram; Leonardo C. de Oliveira; Evandro F. Lima; Isabela de O. Carmo; Sverre Planke; Jessica H. Pugsley; Magda Chmielewska; John A. Howell; David W. Jolley (Journal of South American Earth Sciences, 2024)

Accommodating the role of site memory in dynamic species distribution models - Graziella V. DiRenzo; David A. W. Miller; Blake R. Hossack; Brent H. Sigafus; Paige E. Howell; Erin Muths; Evan H. C. Grant (Ecology, 2021)
First‐order dynamic occupancy models (FODOMs) are a class of state‐space model in which the true state (occurrence) is observed imperfectly. An important assumption of FODOMs is that site dynamics only depend on the current state and that variations in dynamic processes are adequately captured with covariates or random effects. However, it is often difficult to understand and/or measure the covariates that generate ecological data, which are typically spatiotemporally correlated. Consequently, the non‐independent error structure of correlated data causes underestimation of parameter uncertainty and poor ecological inference. Here, we extend the FODOM framework with a second‐order Markov process to accommodate site memory when covariates are not available. Our modeling framework can be used to make reliable inference about site occupancy, colonization, extinction, turnover, and detection probabilities. We present a series of simulations to illustrate the data requirements and model performance. We then applied our modeling framework to 13 yr of data from an amphibian community in southern Arizona, USA. In this analysis, we found residual temporal autocorrelation of population processes for most species, even after accounting for long‐term drought dynamics. Our approach represents a valuable advance in obtaining inference on population dynamics, especially as they relate to metapopulations.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Grain yield, evapotranspiration, and water-use efficiency of maize hybrids differing in drought tolerance - Baozhen Hao; Qingwu Xue; Thomas H. Marek; Kirk E. Jessup; Jacob D. Becker; Xiaobo Hou; Wenwei Xu; Edsel D. Bynum; Brent W. Bean; Paul D. Colaizzi; Terry A. Howell (Irrigation Science, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Breast cancer susceptibility variants alter risk in familial ovarian cancer - A. Latif; H. J. McBurney; S. A. Roberts; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Using bomb radiocarbon analyses to validate age and growth estimates for the tiger shark, Galeocerdo cuvier, in the western North Atlantic - Jeff Kneebone; Lisa J. Natanson; Allen H. Andrews; W. Hunt Howell (Marine Biology, 2008)

Using the composite variables of reproductive morphology, histology and steroid hormones to determine age and size at sexual maturity for the thorny skate Amblyraja radiata in the western Gulf of Maine - J. A. Sulikowski; J. Kneebone; S. Elzey; J. Jurek; W. H. Howell; P. C. W. Tsang (Journal of Fish Biology, 2006)
Age at size was linked to sexual maturity in 77 male and 93 female thorny skates Amblyraja radiata from the western Gulf of Maine using three criteria: 1) gross reproductive morphology, 2) histology and 3) steroid hormone concentrations. Age‐bias plots and the coefficient of variation from vertebral band counts suggested that the ageing method represented a non‐biased and precise approach to the age assessment of A. radiata . Maturity ogives for males, based on data gathered for clasper length, circulating testosterone concentrations and proportion of mature spermatocysts within the testes, predicted that 50% maturity occurred at a total length ( L T ) of 865 mm and c. 10·90 years of age. For females, maturity ogives, based on data gathered for ovary mass, shell gland mass, follicle size and circulating oestradiol concentrations, predicted that 50% maturity occurred at 875 mm L T and c. 11·00 years of age. Collectively, the results suggest that analysis of several contemporaneous reproductive variables offers an accurate determination of sexual maturity in the thorny skate.

Factors affecting the post‐release survival of cultured juvenile Pseudopleuronectes americanus - E. A. Fairchild; W. H. Howell (Journal of Fish Biology, 2004)
Laboratory experiments were performed with cultured and wild juvenile winter flounder Pseudopleuronectes americanus to evaluate differences in behaviour and adaptation affecting post‐release vulnerability to predation. Studies revealed that the cryptic abilities of cultured winter flounder increased over time. Sediment‐naïve, cultured fish required a minimum of 2 days to improve their burying skills and at least 90 days for colour adaptation to match the sediment. Cultured winter flounder selected sediments consisting of small grains and colours matching their own pigment. Cultured winter flounder, regardless of their colour, were significantly more vulnerable to predation by birds. Additionally, cultured fish reacted differently than wild winter flounder when exposed to cues from a potential predator.

Lobster movements in an estuary - W. H. Watson III; A. Vetrovs; W. H. Howell (Marine Biology, 1999)